The Sharia-Based Understanding of Religious Freedom and Women's Rights in Conflict with the Secular Constitutional State - Christine Schirrmacher (Societas Dei: Jurnal Agama dan Masyarakat, 2015)
ABSTRACT: The areas of conflict relating to the freedom of religion and women’s rights do not affect the majority of Muslims who practice their religion in Germany and, in the process, they do not clash with the constitutional state. This is also not a matter having to do with those theologians who take their justification for comprehensive religious freedom and equal rights for women from the Koran and, respectively, other normative sources of Islam. Rather, it has to do with those influential scholars who interpret the norms and commands of Islam in such a way that conflicts arise with the laws of a secular constitutional state. These scholars defend the view that the laws of the Sharia are prior to the norms of the secular constitutional state and are obligatory for all Muslims. At the present moment, the question of freedom of religion could be virtually understood as a topic which, in largely secularized Europe and for the religiously neutral state, possesses little relevance. To what extent do inner-Islamic standpoints interest the constitutional state on the question of religious freedom? For the constitutional state, it does not concern itself with the question of evaluating a religion and its doctrinal content. This also applies with respect to Islam. There, however, where actions are justified by religious convictions, or where they follow from them or are declared to be mandatory by influential religious opinion leaders, and where these actions infringe upon established law or limit the basic rights of individuals, the state and its representatives have to concern themselves with these convictions, independent of whether these convictions are of a religious, political, or of a religious and political nature. KEYWORDS: Germany, Islam, freedom of religion, women’s rights, the constitutional state, conflicts